Reemerging syphilis: diagnosis from oral lesions - Santos, Ingrid da Silva; Bastos, Daniela Brito; Valente, Vitor Bonetti; D'Avila, Solange Pires; Tjioe, Kellen Cristine; Biasoli, Éder Ricardo; Miyahara, Glauco Issamu; Bernabé, Daniel Galera (Journal of Oral Diagnosis, 2017)
Background: Syphilis cases have increasing worldwide recently, indicating a resurgence of the disease. Its clinical features vary widely and often challenge the establishment of the diagnosis. Case report: A 23-year-old woman presented with multiple erosive and patchy oral lesions, dysphagia, and pain with onset of two months. Her medical history revealed that she also presented skin macules which were misdiagnosed as pityriasis by a dermatologist. Nontreponemic test was reagent. An incisional biopsy of an oral lesion was performed and the histopathological aspects were suggestive of syphilis. Treponemic test was positive, confirming secondary syphilis. The treatment consisted of penicillin for 3 weeks. After the 6-months follow-up, clinical and serological exams did not show any sign of the disease. Conclusions: Diagnosing syphilis by oral lesions can be difficult once it can mimic other affections. Additionally, the reemergence of this sexually transmitted disease in the last years demands its inclusion in the differential diagnosis of either erosive or ulcerate lesions.